2016
DOI: 10.1097/mpg.0000000000001036
|View full text |Cite
|
Sign up to set email alerts
|

Liver Disease in Pediatric Patients With Ataxia Telangiectasia

Abstract: Abnormal liver enzymes and fatty liver are common in patients with A-T and may progress to advanced liver disease at a young age. These findings are novel and implicate that patients with A-T with abnormal liver enzymes should be evaluated for the presence of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…A retrospective cohort study of 53 patients with A-T found liver enzyme abnormalities in 43.4% (23/53) and the presence of steatosis by US in 39% (9/23). Liver biopsy was performed in two patients and showed mild to moderate steatosis in both of them and fibrosis in one of them, supporting our results [ 42 ]. Recently, nonalcoholic steatohepatitis without ATM protein in the nucleus of the hepatocytes was showed in a liver biopsy in one A-T patient [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…A retrospective cohort study of 53 patients with A-T found liver enzyme abnormalities in 43.4% (23/53) and the presence of steatosis by US in 39% (9/23). Liver biopsy was performed in two patients and showed mild to moderate steatosis in both of them and fibrosis in one of them, supporting our results [ 42 ]. Recently, nonalcoholic steatohepatitis without ATM protein in the nucleus of the hepatocytes was showed in a liver biopsy in one A-T patient [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our data confirm that elevated serum liver enzymes and hepatic steatosis are frequently encountered in patients with A-T [25][26][27][28] and worsen with age [25]. Although progression to liver fibrosis or cirrhosis is described in the literature [9,25,26], we did not encounter clinically relevant liver function problems in our patients.…”
Section: General Problemssupporting
confidence: 88%
“…While the pathogenesis remains uncertain and the contribution of exogenous factors such as sodium valproate therapy must be recognized, the potential role of BRAT1 impairment, resulting in aberrant mitochondrial function and production of excess reactive oxygen species [So and Ouchi, ], cannot be overlooked. Indeed, similar pathogenic mechanisms are implicated in the development of non‐alcoholic steatohepatitis [Ashraf and Sheikh, ] and hepatic disease has been recently reported in patients with homozygous mutations in ATM [Weiss et al, ]. Furthermore, mitochondrial dysfunction has been observed in muscle biopsy tissue from a patient with BRAT1 ‐related disease [Horn et al, ].…”
Section: Discussionmentioning
confidence: 95%